La santé des personnes âgées francophones vivant en situation minoritaire au Canada : enjeux et besoins - Bouchard, Louise; Desmeules, Martin (Accessibilité et offre active : santé et services sociaux en contexte linguistique minoritaire, 2017)
Résumé L’objectif de ce chapitre est de présenter le profil sociodémographique et sanitaire de la population aînée francophone (65 ans et plus) vivant en situation linguistique minoritaire afin d’en ressortir les enjeux et les besoins qui la caractérisent. Nous aborderons dans un premier temps le fait minoritaire et son effet potentiel sur le vieillissement de la population et la position sociale des personnes âgées, leur santé et leur accès aux services. Une seconde section établira, à partir des données de l’Enquête sur la santé dans les collectivités canadiennes (ESCC, cycles combinés, 2003-2012), le portrait sociosanitaire des aînés en fonction de trois grandes régions canadiennes (les provinces de l’Atlantique, l’Ontario et les provinces de l’Ouest). Enfin, nous discuterons ici de deux enjeux qui nous apparaissent fondamentaux au regard de cette population minoritaire, soit celui de la littératie en santé, c’est-à-dire la capacité de communiquer et de naviguer adéquatement dans le système de santé, et celui de l’offre active de services, une mesure d’équité et de qualité des soins. Mots-clés : aînés francophones, minorités linguistiques, portrait sociosanitaire, Canada, Enquête sur la santé dans les collectivités canadiennes (ESCC).
Chapitre: 5

The health of Francophone seniors living in minority communities in Canada: Issues and needs - Bouchard, Louise; Desmeules, Martin (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)
This chapter presents a profile of the socio-demographic characteristics and the health of Francophone seniors (aged 65 and above) living in minority language communities, and identifies the issues and the needs of this population. In the first section of the chapter, we discuss the minority context and its potential impact on the aging of the population, the social position of seniors, their health, and their access to services. The second section establishes the socio-sanitary profile of Francophone seniors in three large Canadian regions (Atlantic Canada, Ontario, and the West), based on data from the Canadian Community Health Survey—Annual Component (CCHS, combined cycles, 2003–2012). Finally, we discuss two issues that are, we believe, fundamental for this minority population: health literacy—the ability to adequately communicate in and navigate through the health system—and the active offer of services, which is a measure of equity and quality of care for people living in an official language minority community. Key Words: Francophone seniors, linguistic minorities, socio-sanitary portrait, Canada, Canadian Community Health Survey (CCHS).
Chapter: 5

L’expérience des francophones dans l’Est ontarien : importance des personnes pivots (usagers et intervenants) et influence des structures encadrant le système de santé et des services sociaux - Drolet, Marie; Savard, Jacinthe; Savard, Sébastien; Lagacé, Josée; Arcand, Isabelle; Kubina, Lucy-Ann; Benoît, Josée (Accessibilité et offre active : santé et services sociaux en contexte linguistique minoritaire, 2017)
Résumé Le présent chapitre décrit l’expérience d’accès à des services sociaux et de santé en français de francophones de l’Est ontarien. Les expériences et les perspectives de 40 parents, aînés et proches aidants ont été recueillies à l’aide d’entrevues semi-structurées. Une analyse qualitative des verbatim ainsi qu’une analyse visuelle des trajectoires d’un sous-groupe de neuf participants ont permis de faire ressortir les facilitateurs et les défis d’accès aux services en français rencontrés par ces usagers, à partir de leur perspective ou de celle de leur proche aidant. Plus spécifiquement, ce chapitre met l’accent sur les éléments facilitateurs dans le but d’en tirer des leçons pour améliorer les services sociaux et de santé en langue officielle en situation minoritaire. Mots-clés : accès aux services en français, francophones Ontario, recherche qualitative.
Chapitre 6

The experience of Francophones in Eastern Ontario: The importance of key facilitators (service users and providers) and the influence of structures supporting the health and social services system - Drolet, Marie; Savard, Jacinthe; Savard, Sébastien; Lagacé, Josée; Arcand, Isabelle; Kubina, Lucy-Ann; Benoît, Josée (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)
This chapter describes the experiences of Francophones in eastern Ontario in terms of access to social services and health care. The experiences and perspectives of 40 parents, seniors, and caregivers were collected through semi-structured interviews. Qualitative analysis of the transcripts, as well as visual analysis of the trajectories of a subgroup of nine participants, made it possible to identify facilitators and challenges these users experienced in accessing Frenchlanguage services, either from their perspective or that of their caregivers. More specifically, this chapter emphasizes elements that facilitate access; these are discussed in order to share the lessons learned, which can contribute to improvements in social services and health care in official language minority communities. Key Words: access to services in French, Ontario Francophones, qualitative analysis.
Chapter 6

Cognitive health initiative for Francophone seniors in the GTA: Options fo Service Models - Reflet Salvéo; Entité 4 (2017)
Like the general population, the Francophone population is aging and at a faster rate than the population as a whole. While the median age for the Ontario population is 40.1 years, it is 44 for Francophones, and the largest age categories among Francophones are 45-54 and 65 and over: almost one out of five Francophones is included in these age groups. Although the population of the Central Region, including the Greater Toronto Area (GTA), is somewhat younger, the median age of Francophones is still higher than that of the Central Region population as a whole (41.1 vs 39.4) 4. Yet services for people with cognitive disorders and their families and caregivers are fragmented and do not necessarily meet their needs or the demand for service. The situation for those seeking services in French is even worse. Language and culture are key factors in providing quality, safe care. Language barriers constitute a major obstacle for people with dementia and their caregivers and families. Many Francophones lose their second language and revert to their mother tongue as they age, particularly when they are under stress; this is especially true for people coping with dementia. It is essential that Francophones with dementia and their caregivers have equitable access to a continuum of culturally sensitive quality care in French at every stage of the dementia journey. To meet the growing needs of the GTA’s aging Francophone population, the two French language health planning entities, Reflet Salvéo and Entité 4, have partnered on a feasibility study on cognitive health together with the five GTA LHINs (Central West, Mississauga Halton, Toronto Central, Central and Central East), Centres d’Accueil Héritage (CAH) and the Glendon Centre for Cognitive Health. The purpose of the study is to develop options for service models for memory services, including a memory clinic, focussing on very early detection and intervention for mild cognitive impairment but also addressing the need for referrals and supports for those farther along on the dementia journey, and their caregivers. The initiative will build on work previously done on memory centre services in French and on initiatives developed and implemented in the five GTA LHINs. The models proposed will align with LHIN and provincial strategic priorities for dementia and services for seniors and focus on helping people experiencing cognitive decline to remain active participants in their communities for as long as possible. Methodology The first step was a brief analysis of a previous literature review along with a number of studies, reports and plans dealing with the impact of dementia and current service models as well as provincial and LHIN strategic priorities and initiatives for the next several years. Research was also conducted into the availability of services for people with dementia and their caregivers both overall and in French. The next steps involved gaining an overview of existing models and opportunities. As a second stage, interviews were held with LHIN representatives to develop a picture of LHIN priorities and approaches to dementia services in a context of profound system transformation affecting home and community care, primary care and putting the focus on patients, including seniors. Subsequently, following development of a discussion guide, interviews were conducted with health service providers, both those serving the population as a whole and those identified to provide services in French. Another important step was seeking the voice of the Francophone community through a mixture of focus groups and online surveys. Once options are developed, we will go back to providers and the community to seek their input and validate our recommendations. Work on the project as a whole was overseen and supported by a steering committee that included representatives of the two French language health planning entities and the five GTA LHINs as well as the Glendon Centre for Cognitive Health and Centres d’Accueil Héritage (CAH).
fs-ref-orig: Reflet Salvéo, & Entité 4. (2017). Cognitive health initiative for Francophone seniors in the GTA. Options fo Service Models. fs-code-orig: Reflet Salvéo-2017

Étude de besoins sur les foyers de soins de longue durée dans la région du nord-est de l’Ontario - Rapport intérimaire - Réseau du mieux-être francophone du Nord de l’Ontario (2017)
Au début de l’année 2016, le Réseau du mieux-être francophone du Nord de l’Ontario (RMEFNO) a obtenu des fonds afin de mener une étude de besoins sur les foyers de soins de longue durée dans la région du nord-est de l’Ontario. Cette étude, se concluant en mars 2018, a été divisée en deux parties. Ce rapport résume, pour la région du nord-est, les résultats de la première partie, suite à la collecte de données au sujet des francophones et des foyers de soins de longue durée du Nord de l’Ontario. Ce rapport traite des défis auxquels font face les francophones en situation minoritaire résidant dans un foyer de soins de longue durée. Puis, on y discute de soins culturellement adaptés, accompagnés d’exemples de meilleures pratiques tirées de foyers de soins de longue durée de la province. Finalement, des recommandations sont apportées quant aux foyers de soins de longue durée du nord-est. Ces recommandations touchent l’identification et la désignation sous la Loi des services en français, ainsi que les soins culturellement adaptés.
Pages: 25

Needs Study: Long-Term Care Homes in the Northeastern Ontario Region - Interim report - Réseau du mieux-être francophone du Nord de l’Ontario (2017)
Early in 2016, the Réseau du mieux-être francophone du Nord de l’Ontario (RMEFNO) received funding to conduct a needs study regarding long-term care homes in the Northeastern Ontario Region. This two-part needs study is expected to be completed in March 2018. This report summarizes the results of Part 1, for the North East Region, based on the data collected on Francophones and long-term care homes in Northern Ontario. This report covers the challenges faced by Francophones in minority situations who reside in long-term care homes. As well, we touch on culturally appropriate care, and provide examples of best practices gathered from long-term care homes across the province. Finally, we make recommendations regarding long-term care homes in the North East. These recommendations address identification and designation under the French Language Services Act, as well as culturally appropriate care.
pages: 25

Guide de planification et de prestation des soins de longue durée en français. Leçons tirées du pavillon Omer Deslauriers de Bendale Acres et d'autres services de santé en français pour aînés au Canada - Réseau franco-santé du Sud de l’Ontario (2017)
pages: 106

Maintien à domicile : capacité d’offre de services communautaires actuels et futurs au Nouveau-Brunswick - Thériault, Danielle; Dupuis-Blanchard, Suzanne (Service Social, 2017)
La présente étude comporte trois objectifs : 1) déterminer l’état actuel des services offerts pour le maintien à domicile; 2) explorer la nature de la planification des services futurs pour le maintien à domicile; et 3) exposer les défis reliés aux services et les moyens qui s’offrent aux organismes pour que les services répondent le plus efficacement possible aux besoins des personnes âgées francophones. De type séquentiel exploratoire mixte, cette étude a permis de recueillir des données qualitatives pour bonifier des résultats quantitatifs. Quarante-neuf gestionnaires ont répondu au questionnaire en ligne et 11 entrevues ont été réalisées. Huit thèmes communs ont été dégagés en lien avec les objectifs, thèmes qui montrent une préoccupation pour la viabilité des services communautaires en maintien à domicile. Mots-clés : personnes âgées, maintien à domicile, planification, gestion, organismes communautaires, francophones